ROLE OF MULTIDETECTOR COMPUTED TOMOGRAPHY IN ASSESSMENT OF LARYNGEAL CANCER AT HUE CENTRAL HOSPITAL: SHARING EXPERIENCES FROM A SINGLE CENTER FROM 31 CASES - Nguyen , Thi Phuoc Loc; Pham , Nguyen Tuong; Nguyen, Anh Tuan; Le , Xuan Nhan (Tạp chí Điện quang & Y học hạt nhân Việt Nam, 2021)
Background: The role of multidetector computed tomography (MDCT) in diagnosing and staging 31 patients with laryngeal carcinoma. Methods: Patients with laryngeal carcinoma were diagnosed at Hue central hospital from February 2019 to July 2020. Patients were clinically diagnosed patients of laryngeal masses, were first evaluated under indirect laryngoscopy, and then sent for Computed Tomography (CT). Postimaging biopsy was undertaken via direct laryngoscopy. Imaging features of the tumor such as site, level of invasion and staging of tumor were analyzed. Results: The mean age was 61±11 with 90% of patients are male. The risk of laryngeal cancer for those patients who were active smokers (93.5%), and alcohol consumers (67.7%). The most common symptom was hoarseness (93.5%). In CT image, more than half of the cancers were carcinoma of the glottis (29%) and two regions supraglottis and glottis (22,6%), while the less common cancers were the subglottic (3.2%) and all three regions (9.7%) carcinoma, especially true vocal cord (67,7%) is the most common site starting carcinoma. The percentage of tumors spreading to paraglottic space and pre-epiglottic space was 50% and 30.6% respectively. The most common stage of laryngeal cancer in CT was T3 stage (35,5%). There is a weak agreement (Kappa=0.518) in staging in laryngeal cancer in CT compared to laryngoscopy. Conclusion: MDCT is better in staging laryngeal cancer in T3, T4 stages as compared to laryngoscopy.